ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Wiwi Idawati (Universitas Bunda Mulia, 2018)
One of the primary objectives of the company is to maximize the firm value. The firm value is theperception of investors to the company which is mostly related with the stock price. The stock price is formed from investor’s demand and supply of the company’s shares, so the stock price may be used as a proxy for the firm value. This research is meant to test the influence of dividend policy,investment decision, and Return on assets (ROA) to the firm value. The samples of this research are 8 food and beverages companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2016 periods are in accordance with the determined criteria. This research is conducted by using purposive sampling method. The data source of this research has been retrieved from Indonesia Stock Exchange (IDX). The data analysis of this research is done by using regression of data panel analysis with the instrument of Eviews version 8 application . The result of this research shows that the dividend policy has influence to the firm value,investment decision has influence to the firm value, and Return on assets (ROA) does not have any influence to the firm value.Keywords: dividend policy, investment decision , Return on Assets (ROA), firm value.